Genetically Determined EEG Fingerprint of Sleep - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
The influence of genetic factors on the individual profile of sleep electroencephalographic (EEG) power spectra at the 8 to 16 Hz frequency range during non-rapid eye movement (NREM) sleep was determined by recording 40 monozygotic and dizygotic twins during sleep.